Lipid-coated calcium phosphate nanoparticle and beyond: a versatile platform for drug delivery. (28th May 2018) - Huang, Jia-Lin; Chen, Hong-Zhuan; Gao, Xiao-Ling
Abstract: In recent years, lipid-coated calcium-phosphate (LCP) nanoparticle has been developed as a versatile platform for delivery of various therapeutics including gene, protein/peptide, chemotherapeutics and theranostic agents. The high endosomal escape, coupled with the ability to efficiently encapsulate phosphorylated drugs or prodrugs, make LCP become attractive vehicle for drug delivery. Additionally, the principle behind LCP formulation has also allowed rational design of LCP-derived nanoparticles (NPs) with other solid core or lipid membrane to overcome the various drug delivery barriers. Here, we briefly review the history of the development of LCP NPs, highlight the optimisations and modulations in the development process, and summarise the major applications of LCP NPs and LCP-derived NPs in drug delivery.